The implications of the non-farm informal sector for the Vietnamese economy - Slavin, Natali; Stuchlíková, Zuzana, 1979-; Kováčiková, Viera; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
This thesis analyses the problematic of the non-farm informal economy in Viet Nam and outlines its key drivers and nuances in respect to the accelerated economic development after the Đổi Mới reforms. It goes step by step from setting a theoretical groundwork for informality, to introducing distinctive features of informality in Viet Nam specifically, and ultimately to assessing its importance for the Vietnamese labour market. The latter in this thesis stems from a SWOT analysis, where arguments will be set side by side to critically evaluate the sustainability of the non-farm informal sector in Viet Nam from a holistic perspective, i.e. while also acknowledging the benefits it holds for its members and opportunities arising from Viet Nam’s fast-growing export-oriented economy. Finally, several policy recommendations will also be included, to come full circle with the factors in the second chapter.
Vedoucí práce: Zuzana Stuchlíková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses